2017
DOI: 10.24051/eee/76919
|View full text |Cite
|
Sign up to set email alerts
|

Effects of packaging materials and storage periods on seed quality and longevity dynamics of Pericopsis elata seeds

Abstract: This study was carried out to determine the effects of packaging materials and storage periods on seed quality and longevity dynamics of an endangered tropical tree species, Pericopsis elata. The experimental period was December, 2015 to June, 2016. Seed collection was done at the Bobiri Forest Reserve. The seed storage experiment was set up using 3 x 6 factorial arrangements in Completely Randomized Design with three replications. Six packaging materials (jute, nylon, paper, ziplock bag, airtight bottle and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The proteolytic activity of the stored samples has been increased by higher moisture content in this bag. The increase in proteolytic activity leads to the breakage of polypeptide bonds in protein and converted to simple peptide chains that might have decreased the protein content of the sample [ 41 ]. Additionally, the reduction of protein content might be associated with infestation of emmer wheat samples by R .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteolytic activity of the stored samples has been increased by higher moisture content in this bag. The increase in proteolytic activity leads to the breakage of polypeptide bonds in protein and converted to simple peptide chains that might have decreased the protein content of the sample [ 41 ]. Additionally, the reduction of protein content might be associated with infestation of emmer wheat samples by R .…”
Section: Resultsmentioning
confidence: 99%
“…[ 43 ] also reported that storage period had significant effect on rice carbohydrate content. The rapid reduction of carbohydrate content as storage period increased is attributed to the hydrolysis of available carbohydrates into sugars [ 41 ]. Samples from PPBFC, and PPBTX had showed a minor decrease in carbohydrate content during the enhanced storage periods but did not showed any significant difference ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The findings of this study suggested that the interaction between storage method and packaging material was an important factor to consider when choosing a storage method and packaging material for seeds. The choice of storage method and packaging material could have a significant effect on seed quality and longevity (Tandoh et al, 2017). In refrigeration storage, it slows seed metabolism, extending viability and preserving germination potential compared to room temperature storage.…”
Section: Storagementioning
confidence: 99%